Quantification of Focal Outflow Enhancement Using Differential Canalograms - Loewen, Ralitsa T. (Invest Ophthalmol Vis Sci, 2016)
PURPOSE: To quantify regional changes of conventional outflow caused by ab interno trabeculectomy (AIT). METHODS: Gonioscopic, plasma-mediated AIT was established in enucleated pig eyes. We developed a program to automatically quantify outflow changes (R, package eye-canalogram, github.com) using a fluorescent tracer reperfusion technique. Trabecular meshwork (TM) ablation was demonstrated with fluorescent spheres in six eyes before formal outflow quantification with two-dye reperfusion canalograms in six additional eyes. Eyes were perfused with a central, intracameral needle at 15 mm Hg. Canalograms and histology were correlated for each eye. RESULTS: The pig eye provided a model with high similarity to AIT in human patients. Histology indicated ablation of TM and unroofing of most Schlemm's canal segments. Spheres highlighted additional circumferential and radial outflow beyond the immediate area of ablation. Differential canalograms showed that AIT caused an increase of outflow of 17 ± 5-fold inferonasally, 14 ± 3-fold superonasally, and also an increase in the opposite quadrants with a 2 ± 1-fold increase superotemporally, and 3 ± 3 inferotemporally. Perilimbal specific flow image analysis showed an accelerated nasal filling with an additional perilimbal flow direction into adjacent quadrants. CONCLUSIONS: A quantitative, differential canalography technique was developed that allows us to quantify supraphysiological outflow enhancement by AIT.